(untitled) - Bigelow, Stephen J. (New York, NY., 2000)
*Fully revised updated edition. first edition was strong seller - over 30,000 sold.*Ties into the booming A+ Certification market. A+ technicians specialize in PC hardware troubleshooting.*Follows success of Pocket Reference Series by Bigelow, which has sold over 70,000 copies.*Handy format - designed for technicians, in a convenient, portable, pocket-sized edition.*Leading author - Bigelow's last three books have sold well over 250,000 copies.
Keywords: Microcomputers; Maintenance and repair,Handbooks, manuals, etc